Sustainability Disclosure and Profit Management: A Global Systematic Review - Vidara Nanda (Generate Digital Publishing, 2025)
Objectives: This study aims to examine the relationship between sustainability disclosure and earnings management within the framework of legitimacy theory, emphasizing the role of transparency and corporate social responsibility in ensuring ethical financial practices. Research Design & Methods: This study uses the Systematic Literature Review (SLR) method, which includes the stages of planning, implementation, and reporting. In addition, a structured literature review was also applied to group the literature based on themes and historical developments. The inclusion criteria covered scientific articles on Sustainability Reporting (SR) and Earnings Management (EM) with quantitative or mixed methods approaches, published between 2019 and 2024. This period was chosen to capture the current dynamics of the implementation of GRI Standards and their influence on sustainability reporting practices and earnings management. Findings: This analysis reveals that consistent sustainability disclosure strengthens corporate accountability and reduces the likelihood of earnings manipulation. However, the strength of this relationship varies across institutional and regulatory contexts. In developed countries, sustainability reports tend to be more substantive due to strong social and regulatory pressures, while in developing countries, such disclosures often serve a symbolic legitimization purpose. Implications & Recommendations: Policymakers and regulators should encourage standardization and verification of sustainability reporting to enhance its credibility and alignment with ethical financial behavior. Companies are advised to integrate ESG principles into their governance structures to build genuine stakeholder legitimacy and trust. Contribution & Value Added: This study contributes to the literature by providing a comprehensive synthesis of how sustainability disclosure functions as a strategic governance mechanism that restrains earnings management and promotes ethical financial reporting, particularly in diverse institutional environments.